2021
DOI: 10.1115/1.4051220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dielectric Material and Package Stiffness on the Power Generation in a Packaged Triboelectric Energy Harvesting System for Total Knee Replacement

Abstract: The objectives of this study are to experimentally investigate the effects of the dielectric material and the package stiffness on the durability and the efficiency of a previously developed triboelectric-based instrumented knee implant prototype. The proposed smart knee implant may provide useful information about prosthesis health and its functionality after a total knee replacement (TKR) by routine monitoring of tibiofemoral load transfer without the need for any external power source. The triboelectric pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…The relative voltage change remained virtually unchanged after 30 000 dynamic loading cycles, demonstrating the pressure sensor's outstanding mechanical and electrical stability. Our study on the proposed hybrid TPENG revealed minimal voltage deviation (RSD% below 3%) compared to previous studies (earlier studies reported variations with RSD% over 12% for PDMS [20]). In addition, we have introduced a mathematical model and numerical results that are in close agreement with experimental results.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The relative voltage change remained virtually unchanged after 30 000 dynamic loading cycles, demonstrating the pressure sensor's outstanding mechanical and electrical stability. Our study on the proposed hybrid TPENG revealed minimal voltage deviation (RSD% below 3%) compared to previous studies (earlier studies reported variations with RSD% over 12% for PDMS [20]). In addition, we have introduced a mathematical model and numerical results that are in close agreement with experimental results.…”
Section: Discussioncontrasting
confidence: 51%
“…They have been used to create motion or shock sensors [ 17 , 18 ] as well as load sensors. In our previous works [ 19 , 20 ], we examined the performance of TENGs employing different dielectric materials (polydimethylsiloxane (PDMS), fluorinated ethylene propylene (FEP), and polytetrafluoroethylene (PTFE)) with different patterns for self-powered load sensors for TKR at 1000–2000 N of simulated gait loading. One of the major obstacles hindering the practical use of TENGs is the issue of mechanical damage, which occurred for the PDMS layer of previous TENG designs.…”
Section: Introductionmentioning
confidence: 99%
“…Antistatic packaging by the modification of commercial polymers such as polyethylene (PE), PP, and poly (ethylene terephthalate) (PET) is a cost-effective way for solving this problem. [15][16][17] Blending these commercial polymers can improve the purposive properties for antistatic applications such as mechanical properties, film processing, and barrier ability properties. 18,19 Also, in polymer blend nanocomposites the adjustability of morphology due to the segregated structure that is originated from the formation of disperse-matrix or co-continuous morphologies and the tendency of conductive nanoparticles for localization in favorite phase is desirable in academic and industry for fabrication of conductive polymer nanocomposites with widespread applications.…”
Section: Introductionmentioning
confidence: 99%
“…[59] So far, many bonerelated sensing studies are knee implants due to the ease of integration of TENGs and implants. [60][61][62] These studies have explored design, fabrication, and optimization of smart knee implants by integrating TENGs. Ibrahim et al [60] laid the foundation of the smart knee implant using a triboelectric energy harvester.…”
Section: Tengs For Bone-related Sensingmentioning
confidence: 99%